Comunicação política e(m) imagens de si: percursos a caminho do ethos semiotizado - Carreon, Renata de Oliveira (2018)
The changes in social and discursive practices engendered in the last centuries, especially with the advent and popularization of the Internet, have resignified the subject's gaze towards interactivity and connectivity, impelling television to metaphorical perishing and inciting the emergence of social networks. With this change of look, new ways of doing politics emerge, especially if you campaign. Political discourse, now in the face of its mutations, inherently multimodal, gains body, voice and color in videos and photographs and circulates - or to be shared - in an exceptionally bulky way. Mobilizing social networks implies searching for the sale of the candidate in the campaign to construct the images of themselves - ethos. The postings must, in a single step, produce meaning and invite the user to adhere to that discourse, seeking in that user / voter / interlocutor the validation of an ethical world, through credibility or a power to legitimize the discourse: the interlocutor adheres to what is part of his imaginary, to what is established as the good, the right or the honest. Considering, therefore, ethos as a category intrinsically tied to political discourse, we aim to alter the traditional scheme of ethos delineated by Maingueneau, proposing the notion of semiotized ethos, a necessary branching to think the question of verbal and nonverbal, in order to amplify the to look at multimodality discursive and presenting its own methodology for the analysis of diverse materials. It is therefore necessary to undertake a study that understands the visual in the same way that the linguistic is understood, after all, the object must always be the discursive one, without, for this, breaking with the premises that underpin the framework of the discursive studies to which this work becomes affiliated. In order to give substance to such a theoretical undertaking, our material is composed of the campaign of the second round of the presidential elections of 2014, of Dilma Rousseff and Aécio Neves, in the posts in its official profiles of Facebook and in the campaign in the television in the HGPE. The theoretical and methodological bases of the work are anchored in the Discourse Analysis of French orientation, mainly in the writings and rewritten of Dominique Maingueneau